Assessment of Empirical Formulas for Estimating Residual Axial Capacity of Blast Damaged RC Columns - Omran, Mohammad Esmaeilnia; Mollaei, Somayeh (European Journal of Sustainable Development, 2017)
Columns are the most important load bearing structural elements in buildings. Under the effect of external explosions near the building, columns in the ground and first floors may have severe damage that can cause progressive collapse of the whole building frames. Residual axial load bearing capacity of the reinforced concrete column after the effect of lateral blast loading could be a practical criterion to damage assessment of the column. This is essential to determine whether the column has to be replaced or repaired for future use. In this paper, residual axial capacity of the square RC columns under the effect of initial axial force and lateral blast loading is investigated. Explicit finite element package LS-DYNA is used for analysis of the considered models and determining their residual capacity. There are some empirical formulas for estimating of the residual axial capacity of the blast damaged RC columns including Bao and Li (2010), Wu et al (2010) and Arlery et al (2013). Here, FEM results are compared to the estimations of these formulas. Different levels of initial axial force in the columns and different scale distances of blast loading are considered. Keywords: blast loading, reinforced concrete column, residual axial capacity, LS-DYNA.